MARKET REACTION TO BUDGET EFFICIENCY POLICY : AN EVENT STUDY ON HOTEL, RESORT AND CRUISE LINE STOCKS IN INDONESIA - Putu Candra Ardiana Putra; Ida Bagus Separsa Kusuma; Ni Wayan Merry Nirmala Yani (LPPM STIE Muhammadiah Bandung, 2026)
This study aims to analyze the stock market reaction to the announcement of government budget efficiency using abnormal returns and trading volume as proxies for investor response. The research employs an event study method with the Wilcoxon Signed Rank Test to examine differences in averages before and after the announcement. The sample consists of 17 listed stocks in the hotel, resort, and cruise lines sectors in Indonesia. The results indicate that there are no significant differences in average abnormal returns or trading volume around the announcement. This finding suggests that the announcement of government budget efficiency did not trigger a strong market reaction, which may be due to the information being anticipated by investors, its medium- to long-term impact, or a neutral investor response. The results support the semi-strong form of the efficient market hypothesis, where stock prices reflect all relevant public information. This study provides implications for investors and policymakers in understanding market reactions to fiscal policy announcements and can serve as a basis for further research on public policy and capital markets.